Cardiac Remodeling Following Percutaneous Mitral Valve Repair – Initial Results Assessed by Cardiovascular Magnetic Resonance Imaging - Radunski, U. K.; Franzen, O.; Barmeyer, A.; Lange, M.; Lund, G.; Rudolph, V.; Schlüter, M.; Adam, G.; Reichenspurner, H.; Blankenberg, S.; Baldus, S.; Muellerleile, K. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: Percutaneous mitral valve repair with the MitraClip device (Abbott Vascular, Redwood City, California, USA) is a novel therapeutic option in patients with mitral regurgitation. This study evaluated the feasibility of cardiac volume measurements by cardiovascular magnetic resonance imaging (CMR) to assess reverse myocardial remodeling in patients after MitraClip implantation.Materials and Methods: 12 patients underwent CMR at baseline (BL) before and at 6 months follow-up (FU) after MitraClip implantation. Cine-CMR was performed in short- and long-axes for the assessment of left ventricular (LV), right ventricular (RV) and left atrial (LA) volumes.Results: Assessment of endocardial contours was not compromised by the device-related artifact. No significant differences in observer variances were observed for LV, RV and LA volume measurements between BL and FU. LV end-diastolic (median 127 [IQR 96 – 150] vs. 112 [86 – 150] ml/m2; p = 0.03) and LV end-systolic (82 [54 – 91] vs. 69 [48 – 99] ml/m2; p = 0.03) volume indices decreased significantly from BL to FU. No significant differences were found for RV end-diastolic (94 [75 – 103] vs. 99 [77 – 123] ml/m2; p = 0.91), RV end-systolic (48 [42 – 80] vs. 51 [40 – 81] ml/m2; p = 0.48), and LA (87 [55 – 124] vs. 92 [48 – 137] ml/m2; p = 0.20) volume indices between BL and FU.Conclusion: CMR enables the assessment of cardiac volumes in patients after MitraClip implantation. Our CMR findings indicate that percutaneous mitral valve repair results in reverse LV but not in RV or LA remodeling.Key points:• Volume measurements by cardiovascular magnetic resonance imaging are feasible following percutaneous mitral valve repair despite device-related artifacts.• A significant reduction of left ventricular volume was found in terms of beneficial, reverse left ventricular remodeling after 6-month follow-up.• No significant reduction was found in right ventricular or left atrial volumes after percutaneous mitral valve repair after 6-month follow-up.Citation Format:• Radunski UK, Franzen O, Barmeyer A et al. Cardiac Remodeling Following Percutaneous Mitral Valve Repair – Initial Results Assessed by Cardiovascular Magnetic Resonance Imaging. Fortschr Röntgenstr 2014; 186: 951 – 958
Keywords: heart; interventional procedures; MR imaging; artifacts; safety; echocardiography